Fault deformation, seismic amplitude and unsupervised fault facies analysis: Snøhvit Field, Barents Sea. (January 2019) - Cunningham, Jennifer; Cardozo, Nestor; Townsend, Christopher; Iacopini, David; Wærum, Gard Ole
Abstract: We present an integrated seismic imaging and fault interpretation workflow to characterize the seismic expression in and around an E-W trending central fault system imaged in near-angle stack seismic data of the Snøhvit Field, Barents Sea. Three E-W normal fault systems offset five Triassic-Lower Cretaceous seismic horizons across the field. Fault throw is largest at depth and decreases with shallowing. Dip distortion (DD) decreases in magnitude and extent with shallowing. Fault enhancement (FE), a filter used to detect edges, was applied on a blend of tensor, semblance and dip attributes, and allowed us to classify fault zones into four unsupervised seismic fault facies (mid-high FE). High FE facies occur at the center of the fault zones and are abundant in the highest thrown eastern part of the field. The FE facies decrease radially outwards field wide. Facies correlate with throw and dip separation gradient, which are in turn related to mechanical stratigraphy controlling fault propagation. We observe systematic seismic amplitude variations: a major amplitude drop on the fault plane, and a brightening and dimming linked to fault-related synclines and anticlines, respectively. Our workflow establishes a methodology for fault interpretation, linking fault throw, DD, seismic attributes and fault facies classification. Highlights: A fault analysis workflow was applied on seismic from the Snøhvit Field, Barents Sea. E-W trending faults show highest dip distortion and throw in east of study area. A fault enhancement filter was used to classify unsupervised seismic fault facies. Seismic amplitudes present systematic brightening and dimming when nearing faults. Fault facies correlate with throw, displacement gradient and mechanical stratigraphy.